PENINGKATAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH MANAJEMEN KELAS DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS RIAU - Hendri Marhadi; Erlisnawati Erlisnawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Problem in this research was students achievement still low with average value 64,13. The purpose of this research was to improve the students’ achievement of in Management Class with the implementation of cooperative learning model type group investigation. This research was an classroom action research with two cycles in third semester 2014/2015. After implementation of cooperative learning model type group investigation, students’ achievement average on UH I with average 70,28 improved 9,6%. Students’ achievement on UH II was average 78,15 that improved 21,9%. Teacher’s activities with the implementation of cooperative learning model type group investigation in first meeting of first cycle was 62,5& (good category), and second meeting 78% (good category) in second meeting that improved 12,5 point. At second cycle, teacher’s activities in first meeting was 87,5% (verygood category) that improved 9,38 point from second meeting of first cycle. In second meeting was 93,8% (verygood category) which improved 6,3 point. Students’ activities in first meeting of first cycle was 65,6% (good category), and meeting second 75% (good category) in second meeting that improved 9,4 point. At second cycle, students’ activities in first meeting was 81% (very good category) that improved 6 point from second meeting of first cycle. Second meeting cycle second 90,6% (verygood category) in second meeting, which improved 9,6 point. Implementation of cooperative learning model type group investigation can improved students’ achievement in management class.Keywords: cooperatif group investigation, students achievement